EEG spectral analysis of attention in ADHD: implications for neurofeedback training? - Heinrich, Hartmut; Busch, Katrin; Studer, Petra; Erbe, Karlheinz; Moll, Gunther; Kratz, Oliver (Frontiers in Human Neuroscience, 2014)
In children with attention-deficit/hyperactivity disorder (ADHD), an increased theta/beta ratio in the resting EEG typically serves as a rationale to conduct theta/beta neurofeedback (NF) training. However, this finding is increasingly challenged. As NF may rather target an active than a passive state, we studied the EEG in a condition that requires attention.In children with ADHD of the DSM-IV combined type (ADHD-C; N = 15) and of the predominantly inattentive type (ADHD-I; N = 9) and in typically developing children (N = 19), EEG spectral analysis was conducted for segments during the attention network test (ANT) without processing of stimuli and overt behavior. Frontal (F3, Fz, F4), central (C3, Cz, C4) and parietal (P3, Pz, P4) electrodes were included in the statistical analysis. To investigate if EEG spectral parameters are related to performance measures, correlation coefficients were calculated.Particularly in the ADHD-C group, higher theta and alpha activity was found with the most prominent effect in the upper-theta/lower-alpha (5.5-10.5 Hz) range. In the ADHD-I group, a significantly higher theta/beta ratio was observed at single electrodes (F3, Fz) and a tendency for a higher theta/beta ratio when considering all electrodes (large effect size). Higher 5.5-10.5 Hz activity was associated with higher reaction time variability with the effect most prominent in the ADHD-C group. A higher theta/beta ratio was associated with higher reaction times, particularly in the ADHD-I group.(1) In an attention demanding period, children with ADHD are characterized by an underactivated state in the EEG with subtype-specific differences. (2) The functional relevance of related EEG parameters is indicated by associations with performance (reaction time) measures. (3) Findings provide a rationale for applying NF protocols targeting theta (and alpha) activity and the theta/beta ratio in subgroups of children with ADHD.
EVALuna2:23879

Refining the picture of reduced alerting responses in ADHD - a single-trial analysis of event-related potentials - Heinrich, Hartmut; Busch, Katrin; Studer, Petra; Erbe, Karlheinz; Moll, Gunther; Kratz, Oliver (Neuroscience Letters, 2014)
In attention-deficit/hyperactivity disorder (ADHD), a reduced phasic alerting response (event-related potential component P3 to cue stimuli) has been reported for different subtypes and task types in a series of studies. In order to get a refined picture of this attentional deficit, which is based on the analysis of averaged event-related potentials, we studied the distribution of single-trial cue-P3 amplitudes and the relation between the cue-P3 and the neural state (EEG spectral analysis) when expecting the stimulus. Brain electrical activity was recorded in children of different ADHD subtypes (combined type, predominantly inattentive) and typically developing children while conducting the attention network test. In children with ADHD of the combined type, smaller cue-P3 amplitudes in the averaged signal were due to a larger portion of single trials with reduced cue-P3 amplitudes whereas maximum amplitudes did not differ from typically developing children. In this ADHD subtype, larger activity in the upper theta/lower alpha range (5.5-10.5Hz) was strongly associated with the range (difference between 0.9 quantile and 0.1 quantile) of the cue-P3 amplitude in single trials (correlation coefficient r=0.77) indicating a suboptimal neural state before stimulus presentation. In children with ADHD of the predominantly inattentive subtype, single-trial P3 amplitudes were comparable at lower quantiles but maximum amplitudes were reduced. This result pattern indicates an intact triggering of the cue-P3 but a reduced capacity of resource allocation for the predominantly inattentive subtype. Though findings are limited by a relative small sample size, the cue-P3 may be considered as a neurophysiological marker of alerting deficits in ADHD reflecting different underlying mechanisms in ADHD subtypes.
EVALuna2:23877